Employment Relationships in China: Do Workers Relate to the Organization or to People? - Hui, Chun; Lee, Cynthia; Rousseau, Denise M. (Organization Science, 2004)
This study investigates the contribution of organizational support and personal relations in accounting for Chinese workers' affective commitment to the organization for which they work and their organizational citizenship behavior. In a sample of 605 matched cases of employees and their immediate supervisors from a large, reformed state-owned firm, organizational support was found to relate to affective commitment more strongly than to organizational citizenship behavior. Personal relations, however, were found to relate similarly to affective commitment and organizational citizenship behavior. Moderator effects are evident with the less-traditional Chinese employees manifesting greater citizenship behavior than do more-traditional Chinese, in response to a high-quality relationship with their supervisor. More-traditional Chinese contribute citizenship behavior that is moderately high, regardless of the quality of their relationship with their supervisor. These findings suggest a need to revise certain assumptions regarding the nature of the employee-employer exchange relationship in China and in similar transitional societies.